FEM/Wideband FMBEM coupling based on subdivision isogeometry for structural-acoustic design sensitivity analysis - Chen, Xiuyun; Huang, Yajun; Zhou, Zhongbin; Xu, Yanming (Frontiers in Physics, 2023)
A computer simulation approach known as the isogeometric (IGA) method may directly use the surface information of geometric model. In 3D computer graphics, Loop subdivision surfaces are a common method for creating complicated shapes. In this study, we propose a coupling algorithm that utilizes Loop subdivision surfaces and a direct differentiation method for the computation of acoustic-fluid-structure interaction and the performance of structural-acoustic sensitivity analysis. This algorithm combines the finite element method (FEM) and wideband fast multipole boundary element method (FMBEM). Because of that the proposed method is of a great ability of integrating the numerical calculation and computer-aided modeling, the current technique can deliver results quickly and accurately. The numerical prediction of the effects of vibrating structures with arbitrary shape within sound field is made feasible by the FEM/Wideband FMBEM technique. Calculation examples are provided to show the applicability and effectiveness of the suggested method.